Treatment of giardiasis in dogs: field clinical study to confirm the efficacy, safety, and acceptance of a metronidazole-based flavored oral suspension - Sloane Jones; Philippe Briantais; Cristiano Von Simson; Eleonore De Meyrignac; Laure Poincelot; Delphine Rigaut (Parasites & Vectors)
Abstract Background Giardia duodenalis is a prevalent gastrointestinal parasite in dogs, causing diarrhea, vomiting, and weight loss. Metronidazole is a common treatment for this infection. This study aimed to evaluate the efficacy, safety, and acceptance of a flavored liquid metronidazole oral suspension in treating G. duodenalis in naturally infected dogs. Methods A double-masked, vehicle-controlled, randomized, multi-center clinical field trial was conducted. Client-owned dogs with confirmed G. duodenalis infections were enrolled and randomized into AYRADIA-treated and control groups. The AYRADIA group received the metronidazole suspension at 0.2 ml/kg twice daily for 5 days, while the control group received a flavored vehicle suspension without metronidazole. Fecal samples were collected before and after treatment to assess G. duodenalis cyst counts. Clinical examinations and owner assessments were also performed to evaluate safety and treatment acceptance. Results The study enrolled 180 dogs, with 129 included in the efficacy analysis. AYRADIA treatment resulted in a 99.92% reduction in G. duodenalis cyst counts, significantly higher than the reduction in the control group. Adverse events were similar between both groups (10%), mainly consisting of diarrhea and vomiting. The treatment was readily accepted by 99% of dogs. Conclusions AYRADIA, administered at 0.2 ml/kg twice daily for 5 days, is highly effective in treating G. duodenalis infections in dogs. The treatment demonstrated a positive safety profile and excellent acceptance. This flavored oral suspension offers a valuable and convenient option for veterinarians managing giardiasis in dogs. Graphical Abstract